(untitled) (Bangladesh Journal of Medical Science, 2013)
Objective: The objective of this study was to identify the outcomes of short term inspiratory muscle training (IMT) combined with chest physiotherapy (CP) on lung function, inspiratory muscle strength, exercise tolerance and quality of life of COPD patients. Materials and Methods: This randomized-controlled trial was conducted at the Terendak Armed Forces Hospital, Melaka. Eighteen hospitalized COPD patients (FEV1 50% to = 80% predicted) were randomized into intervention (IG) and control group (CG). The IG received IMT and CP treatments whilst the CG received only CP for a period of 4 weeks. Assessments of lung function (FEV1/FVC), inspiratory muscle strength (PImax), exercise tolerance (6MWT) and quality of life (SGRQ score) were taken at baseline and after 4 weeks. Results: Analysis showed IG group increased in FEV1/FVC by 19.4%, PImax by 54.7%, 6MWT by 33.2% and quality of life by 52.6% (All, p<0.05). The control group increased in FEV1/FVC by 8.7% (p>0.05), PImax by 15% (p<0.05), 6MWT by 18.9% (p<0.05) and quality of life by 15.6% (p<0.05). Conclusion: The present study has established that by combining inspiratory muscle training (IMT) and chest physiotherapy, provides superior effects on lung function, inspiratory muscle strength, exercise tolerance and quality of life among COPD patients. DOI: http://dx.doi.org/10.3329/bjms.v12i4.13302 Bangladesh Journal of Medical Science Vol. 12 No. 04 October 13 Page 398-404